2016
DOI: 10.1042/bcj20160164
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain acylcarnitines determine ischaemia/reperfusion-induced damage in heart mitochondria

Abstract: The accumulation of long-chain fatty acids (FAs) and their CoA and carnitine esters is observed in the ischaemic myocardium after acute ischaemia/reperfusion. The aim of the present study was to identify harmful FA intermediates and their detrimental mechanisms of action in mitochondria and the ischaemic myocardium. In the present study, we found that the long-chain acyl-CoA and acylcarnitine content is increased in mitochondria isolated from an ischaemic area of the myocardium. In analysing the FA derivative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
103
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(119 citation statements)
references
References 47 publications
6
103
0
Order By: Relevance
“…4). Overall, we find that the headgroup of fatty acids tend to show a higher percentage of hydrogen bonding with Lys 45 or Lys 63 than their respective acylcarnitines (Fig. 4).…”
Section: Molecular Dynamic Simulations Of the Various Ligands In Thementioning
confidence: 78%
See 4 more Smart Citations
“…4). Overall, we find that the headgroup of fatty acids tend to show a higher percentage of hydrogen bonding with Lys 45 or Lys 63 than their respective acylcarnitines (Fig. 4).…”
Section: Molecular Dynamic Simulations Of the Various Ligands In Thementioning
confidence: 78%
“…In MD simulations, the carboxyl headgroup in LCFA and long-chain acylcarnitines (i.e. C12 or longer) exhibited hydrogen-bonding interactions with Lys 45 or Lys 63 . The results showed that these headgroups switched between Lys 45 and Lys 63 during the 100-ns simulation, with an average dwelling time on the order of 25 ns.…”
Section: Molecular Dynamic Simulations Of the Various Ligands In Thementioning
confidence: 99%
See 3 more Smart Citations